Novel etching protocol for epidote fission tracks - Nakasuga, Wagner Massayuki [UNESP]; Tello Saenz, Carlos Alberto [UNESP]; Campos Curvo, Eduardo Augusto; Hadler Neto, Julio Cesar; Guedes, Sandro; Resende, Rosana Silveira [UNESP] (Elsevier, 2018)
Along the years, etching for fission tracks was a major issue in the development of the epidote fission track dating. It was not a consensus in the scientific community. As an attempt to mitigate it, we present a novel etching protocol (HF 40% at 15 °C for 80 min) and test it in ten different natural samples etched with HF 40% at 15 °C for 80 min (nine epidotes and one clinozoisite). The samples had their chemical compositions determined, forming a database for epidote chemical compositions. Fission tracks were observed in five samples. The uranium content in the remaining four samples was too low and hence tracks could not be observed. Further analyses, Raman and uranium concentration, confirm this observation. Fission tracks were not observed in clinozoisite sample. The proposed etching protocol showed to be less hazardous and efficient to etching fission tracks in epidote.
Keywords: Clinozoisite; Epidote; Etching